Optimal Control of Second Order Neutral Stochastic Integro Differential Equations with Impulses Driven by fBm - Madhuri, S.; Deekshitulu, G.V.S.R. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we introduce the optimal control problem for second order impulsive stochastic integro differential equations with infinite delay driven by fractional Brownian motion in Hilbert spaces. By using stochastic analysis theory and Krasnoselskii-Schaefer type fixed point theorem existence of mild solution is established. Next, conditions for the existence of optimal pair for these systems is also derived. Finally an example is given to illustrate theoretical results.